A disynaptic basal ganglia connection to the inferior olive: potential for basal ganglia influence on cerebellar learning - Ruigrok, Tom J. H.; Wang, Xiaolu; Sabel-Goedknegt, Erika; Coulon, Patrice; Gao, Zhenyu (Frontiers in Systems Neuroscience, 2023)
Recent studies have shown that the cerebellum and the basal ganglia are interconnected at subcortical levels. However, a subcortical basal ganglia connection to the inferior olive, being the source of the olivocerebellar climbing fiber system, is not known. We have used classical tracing with CTb, retrograde transneuronal infection with wildtype rabies virus, conditional tracing with genetically modified rabies virus, and examination of material made available by the Allen Brain Institute, to study potential basal ganglia connections to the inferior olive in rats and mice. We show in both species that parvalbumin-positive, and therefore GABAergic, neurons in the entopeduncular nucleus, representing the rodent equivalent of the internal part of the globus pallidus, innervate a group of cells that surrounds the fasciculus retroflexus and that are collectively known as the area parafascicularis prerubralis. As these neurons supply a direct excitatory input to large parts of the inferior olivary complex, we propose that the entopeduncular nucleus, as a main output station of the basal ganglia, provides an inhibitory influence on olivary excitability. As such, this connection may influence olivary involvement in cerebellar learning and/or could be involved in transmission of reward properties that have recently been established for olivocerebellar signaling.